Determinants of International Educational Experiences in Private Universities - Peng, Lan; Amponstira, Fuangfa (Journal of Dhamma for Life, 2026)
International educational experiences have become a critical component of higher education, providing students with global competencies, intercultural awareness, and enhanced employability. However, private universities often face significant constraints that shape their ability to offer robust international programs. This quantitative study investigates the factors influencing international educational experiences in private universities, focusing on four key dimensions: Institutional Support, Financial Resources, International Partnerships, and International Learning Readiness. A structured questionnaire was administered to 400 undergraduate students enrolled in private universities with existing internationalization initiatives. Data were analyzed using Structural Equation Modeling to determine the direct and indirect effects of each factor on students’ international participation. Results indicate that Institutional Support and International Partnerships have a strong positive impact on students perceived accessibility to international programs, while Financial Resources remain the most significant barrier. International Learning Readiness, particularly English proficiency, cultural readiness, and motivation, was found to be a critical determinant of intention to participate in international programs. The final SEM model demonstrated good fit indices (CFI > 0.95, RMSEA < 0.06), supporting the theoretical framework. The study highlights the need for private universities to develop stronger institutional systems, expand sustainable partnerships, and increase financial aid mechanisms to improve program accessibility. Recommendations include strategic investment in international offices, expanding scholarship programs, and implementing pre-departure training initiatives. Overall, this research contributes empirical evidence supporting policy formulation and internationalization strategies in private higher education.